DISABILITY, DIVERSITY AND DIFFERENCE: IDIOSYNCRASIES AND CONCEPTUAL DIFFERENCES - Susann Souza da Silva, Jackeline (2021)
Due to different historical circumstances, the Brazilian political and legal regulation for inclusion has expanded considerably in recent decades. Such regulations bring transversal guidelines in favor of specific identity groups such as people with disabilities, women and ethnic-racial groups. Since 1980, the United Nations (UN) has played a leading role in disseminating international guidelines against violence, discrimination and deprivation that put people and social groups at multiple risks. Therefore, there is the consensus that inclusion is a regulating principle of nations. It is a fact that inclusion is an emerging agenda facing the complex picture of social barriers and exclusions. However, public discourses, of international agencies and government leaders, in defense of inclusion and diversity present idiosyncrasies and contradictions that even camouflage political intentions disconnected from collective struggles. In this perspective, this article aims to characterize the conceptual differences between disability, diversity and human difference in order to reflect on how these concepts are related in social dynamics. It is concluded that the definitions, objects of analysis, are situated in the same political debate, but each term configures its own ideological foundations that sometimes align with the critical perceptions of the discourse, sometimes reproduce the normative view of subjects-body-minds, naturalizing, often subtly, the rhetoric of subalternity in the relationship between the dominant and the dominated.